The Idea of Rome beyond Rome - Uscatescu, Alexandra (Actual Problems of Theory and History of Art, 2025)
The weight of the Classical culture during the Middle Ages is undeniable and in this context, Roman art seems to play two opposing roles: the basis for the development of mediaeval art and a privileged source from which models are extracted. The issue is rather complex, so this argument will be supported by a single iconographic element embedded in the discourse of the idea of Rome: the she-wolf and the twins. This icon summarizing the idea of Rome survived its destruction and was adopted by other peoples alien to the Roman Empire. This paper is focused on the reception and re-use of that icon by Anglo-Saxon, Frank or Lombard peoples, between 5th and 9th centuries.
Keywords: Anglo-Saxons; iconography; Late Antiquity; Lombard; Lupa Romana; Romulus and Remus; Sogdian; visual culture